Soft Skills for Learning Biology in a Foreign Language in Digital Environments - Flores-González, Efigenia (Forum for Linguistic Studies, 2025)
In a technological society, the adaptability of students and the need for interaction demand collaborative work, self-esteem, time management, and problem-solving skills. Considering the above, the inclusion of digital skills is essential because students often face difficulties in virtual modalities and sometimes fail to reach the expected conceptual-linguistic performance. This study aims to identify the impact of soft skills on learning biology in a foreign language in virtual environments. For this, a quantitative, correlational, and cross-sectional approach was followed, obtaining the following results: the management of emotions, interpersonal communication, critical thinking, autonomy and knowledge of the use of technology are elements that positively affect the conceptual learning of biology in English as a foreign language (EFL) since they allowed to analyze, evaluate and synthesize the information in virtual classrooms thanks to the emotional competence. Indeed, it reduces stress, avoids anxiety or frustration, and develops interpersonal communication skills for empathic, responsible, self-regulated, and autonomous interactions. All these elements contributed to the adaptation of such environments with motivational dyes based on collaborative work. The correlation between soft skills and learning biology in EFL was positive and strong. It helps to corroborate the hypothesis, pointing out that the more students apply soft skills in their learning process, the better their academic performance will be. In conclusion, socio-affective skills are a fundamental complement to cognitive skills. Above all, the contribution focuses on the functionality and influence of soft skills in online learning processes to foster high-quality praxis and their inclusion in educational programs.